The Effect of Digital Mindfulness Interventions on Depressive, Anxiety, and Stress Symptoms in Pregnant Women: A Systematic Review and Meta-Analysis - Monique L. Mefrouche; Eva-Maria Siegmann; Stephanie Böhme; Matthias Berking; Johannes Kornhuber (MDPI AG, 2023)
Introduction. Pregnancy is a unique time in a woman's life that can be both exciting and challenging. It is also a period that can be associated with significant stress, anxiety, and depression, which can have negative consequences for both the mother and the baby. Mindfulness interventions are known to be a well-suited treatment and prevention method for psychiatric symptoms in pregnancy, and web-based applications have been explored. We here present an up-to-date systematic review and meta-analysis of randomized-controlled trials to investigate the effect of digital-based mindfulness interventions on depressive, anxiety, and stress symptoms during pregnancy. Methods. The systematic literature search and data extraction was performed by two independent raters. It resulted in 13 eligible studies overall comprising 1373 participants. We conducted random-effects meta-analyses for depressive, anxiety, and stress symptoms after completion of a digital mindfulness intervention (compared to a control group). Results. Digital mindfulness intervention methods were significantly able to reduce depression (g = −0.47, 95% CI [−0.9; −0.09]) and anxiety symptoms (g = −0.41, 95% CI [−0.77; −0.05]), but not stress symptoms. These effects were moderated by the attrition rate (βDepression = 0.025, pDepression < 0.01; βAnxiety = 0.022, pAnxiety < 0.01; βStress = 0.022, pStress < 0.01). Primiparity also had a significant influence on the intervention effect regarding depression symptoms (β = 0.033, p = 0.024). Conclusions. Digital mindfulness interventions are a promising method to reduce mental health symptoms in pregnant women. We identified certain parameters moderating this effect, for example, primiparity and the attrition rate.